2021
DOI: 10.1080/00222895.2021.1933886
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pitch on Tempo-Spatial Accuracy and Precision in Intercepting a Virtually Moving Ball

Abstract: The project was supported by the German Research Foundation (DFG) with two grants awarded to Markus Raab (RA 940/15-2) and Rouwen Cañal-Bruland (CA 635/2-2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Bedford, 2001; Van Wassenhove et al, 2007), observers tend to attribute stimuli from different modalities to the same event resulting in the so-called unity assumption (cf. Jackson, 1953; Welch & Warren, 1980). However, an observer's assumption of unity does not necessarily imply that stimuli from different sensory sources contribute to perception to an equal extent.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bedford, 2001; Van Wassenhove et al, 2007), observers tend to attribute stimuli from different modalities to the same event resulting in the so-called unity assumption (cf. Jackson, 1953; Welch & Warren, 1980). However, an observer's assumption of unity does not necessarily imply that stimuli from different sensory sources contribute to perception to an equal extent.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are a plethora of studies suggesting that different sensory modalities interact and may even interfere with each other (for an overview, see Shimojo & Shams, 2001). In particular, there is evidence that the perceived intensity of a stimulus in one sensory modality is modulated by the simultaneous presentation of a second stimulus in another sensory modality (Sanabria et al, 2007; Shipley, 1964)—a phenomenon referred to as intersensory bias (Lukas et al, 2014; Welch & Warren, 1980). Following Welch and Warren (1980), the strength of intersensory bias is defined by structural factors (e.g., spatiotemporal discrepancy or coincidence) and cognitive factors (e.g., awareness on intersensory discrepancies, assumption of unity, compelling [i.e., stimulating] features of the situation).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the modality of stimulus presentation, future research about the differences in sensitivity towards spatial and temporal information may also focus on the auditory modality, as it has been shown that the auditory system is more dominated by temporal than by spatial information (O'Connor and Hermelin 1972;Recanzone 2009). It follows that another way to test the hypothesis we sought to shed light on in this paper, may be to manipulate the quality of auditory information, thereby testing the counterpart of the hypothesis, namely that reductions of auditory qualities should more strongly affect temporal than spatial precision (Tolentino-Castro et al 2021).…”
Section: Additional Factors and Limitationsmentioning
confidence: 95%